DEVELOPMENT OF PURE CULTURE STARTER FOR KECAP, AN INDONESIAN SOY SAUCE [Pengembangan Ragi Kecap Khas Indonesia Dengan Biakan Murni] - Joko Sulistyo; Sayuki Nikkuni (BERITA BIOLOGI, 2005)
In order to prevent aflatoxin contamination during the production of kecap, an Indonesian soy sauce, a white-spored mutant K-IA strain induced from an aflatoxin-negative koji mold was applied to koji making process of kecap. While kecap koji making process took 9 days by conventional method without inoculum, the use of K-IA strain as a starter shortened the process to 3 days at room temperature. The koji prepared with this starter contained 2.3 x 107 cfu/g of Aspergillus sp. K-IA as the dominant speciesand some contaminants from the environment such as other species of Aspergillus (2.0 x 10 cfu/g) and Mucorales (1.4 x 10s cfu/g). The mash prepared with kecap koji inoculated with this starter contained higher formol nitrogen (FN) and water-soluble nitrogen (WN) than those prepared with koji inoculated without any starter.These results demonstrated that the use of this starter did not only contribute to the prevention of aflatoxin contamination but also improved the conventional kecap fermentation process.